Implementasi Partisipasi Masyarakat dalam Penerapan Peraturan daerah Kabupaten Gorontalo Nomor 04 Tahun 2014 Tentang Penertiban Hewan Ternak di Desa Ilomata (International Forum of Researchers and Lecturers, 2023)
The purpose of this study is to analyze the implementation of community participation in the application of Gorontalo District Regulation Number 04 of 2014 concerning the Control of Livestock in Ilomata Village and the factors that influence it. The research method used in this research is empirical legal research. The results of this study indicate that the implementation of community participation in the Implementation of Regional Regulations of Gorontalo Regency Number 04 of 2014 concerning Controlling Livestock in Ilomata Village has not been optimal because socialization in the formation and implementation of regional regulations has not been thorough and breeders have not fully known and understood these regional regulations. Enforcement of regional regulations is also not fully optimal and the provision of livestock facilities is inadequate.